2015
DOI: 10.1038/leu.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and long-term outcome of 217 young patients with essential thrombocythemia or early primary myelofibrosis

Abstract: We investigated the influence of molecular status on disease characteristics and clinical outcome in young patients (⩽ 40 years) with World Health Organization (WHO)-defined essential thrombocythemia (ET) or early/prefibrotic primary myelofibrosis (early-PMF). Overall, 217 patients with ET (number 197) and early-PMF (number 20) were included in the analysis. Median follow-up time was 10.2 years. The cumulative incidence of thrombosis, hemorrhages and disease evolution into myelofibrosis/acute leukemia were 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 33 publications
3
38
0
2
Order By: Relevance
“…6,7 Recent studies have suggested that CALR-positive ET can be considered a distinct clinical entity from JAK2 V617F -positive ET because of higher platelet counts and a lower incidence of thrombosis in the former. [8][9][10][11][12] This observation is especially relevant with regard to the use of antiplatelet therapy in CALR-mutated low-risk ET patients, in whom the increased risk of bleeding associated with higher platelet counts might offset the benefits of reducing the relatively low risk of thrombosis.…”
Section: Jak2mentioning
confidence: 99%
“…6,7 Recent studies have suggested that CALR-positive ET can be considered a distinct clinical entity from JAK2 V617F -positive ET because of higher platelet counts and a lower incidence of thrombosis in the former. [8][9][10][11][12] This observation is especially relevant with regard to the use of antiplatelet therapy in CALR-mutated low-risk ET patients, in whom the increased risk of bleeding associated with higher platelet counts might offset the benefits of reducing the relatively low risk of thrombosis.…”
Section: Jak2mentioning
confidence: 99%
“…Qualitative assessment of JAK2V617F mutation was performed as described elsewhere [19]; JAK2V617F allele burden was assessed in granulocyte DNA by quantitative polymerase chain reaction-based allelic discrimination assay (Ipsogen JAK2 MutaQuant Kit) on 7900 HT Fast Real Time PCR System (Applied Biosystem).…”
Section: Introductionmentioning
confidence: 99%
“…CALR mutations identified by NGS were confirmed by Sanger sequencing. MPL mutations were investigated by ipsogen MPLW515K/L MutaScreen Kit and by Sanger sequencing (for MPLS505N and other secondary exon 10 mutations), as previously described [55]. Additional masking mutations in JAK2 exon 14 were investigated by Sanger sequencing [39].…”
Section: Methodsmentioning
confidence: 99%
“…Additional masking mutations in JAK2 exon 14 were investigated by Sanger sequencing [39]. In case of clinical suspicion of PV, JAK2 exon 12 mutations were also tested by Denaturing High Pressure Liquid Chromatography (DHPLC) and confirmed by Sanger sequencing [5558]. Diagnoses of all hematological diseases were made according to the WHO2008 criteria [1].…”
Section: Methodsmentioning
confidence: 99%